ANALISIS RETURN FLOW ANTAR BENDUNG (Studi Kasus Bendung Klampok-Plakaran dan Bendung Sekarsuli) - , CUT DWI REFIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Weir is one of the solutions to cope with the problem of water deficiency for areas afar from water source (river). However, it may also be potential to generate other problems, such as the decrease or even the disappearance of the water at the downstream area. This is different to the on field where the discharge of weir on the downstream area is larger than the discharge weir on the upstream area. This indicates the return flow phenomenon. Such phenomenon occures due to the tapping of the flow for irrigation purpose and some of the flow which is not utilized for the irrigation comes back to the river in the form of run-off and seepage. The overviewed weirs within this study include the Klampok-Plakaran and Sekarsuli weirs. The return flow analysis was carried out by using the Tank Model. The form of the model was adjusted to the condition on field, such as paddy fields, cane plantation and fish ponds. The inputs for this model were the rainfall and water irrigation distribution. The output included the evaporation, evapotranspiration, runoffs, seepage and percolation. The parameters in the Tank Model were the output coefficient from the side and below, and the height of reservation in the tank. Output from the side of the tank consisted of runoffs and seepage, which were the return flow value. The Tank Model was calibrated and verified to obtain the most proper Tank model suitable to the condition on field. The accuracy indicator of the model showed similarity between simulated and measured return flow. The accuracy indicators of the Tank Model consists of correlation coefficient (R), volume error (VE), and root mean square error (RMSE) of 0,97